Implementation of Good Governance Principles in Public Services Through Law Enforcement Against Maladministration - Tampubolon, Dedy Aprianto; Defran Sukma Wijaya; Julia Anggraini; Dafyar Eliadi Hardian (LifeSciFi, 2025)
Quality public services are a reflection of good governance. However, in practice, there are still many acts of maladministration that hinder the realization of fair, transparent, and accountable services. This study aims to analyze the implementation of good governance principles in public services, especially through law enforcement against various forms of maladministration. The method used is a juridical-sociological approach by examining normative legal data and empirical conditions in the field. The results of the study indicate that the implementation of good governance principles such as transparency, accountability, participation, effectiveness, and the rule of law is still not optimal in a number of public service sectors. One of the main causes is weak supervision and lack of assertiveness in law enforcement against administrative violations by state officials. Therefore, it is necessary to strengthen the public complaint mechanism, the active role of supervisory institutions such as the Ombudsman, and strict law enforcement to encourage bureaucratic reform and public services with integrity. This study concludes that law enforcement against maladministration is a strategic instrument in realizing the principle of good governance substantially in public services.